Die Entwicklung des Formatradios in Deutschland Eine Untersuchung zur Konvergenzhypothese im Hörfunk - Heckl, Harald (Nomos Universitätsschriften - Medien und Kommunikation, 2022)
Are German music-based radio stations really converging and offering the same kind of content? Is there actually no difference between the stations? Do their content and music really appeal to their target group? And does the perfect flow of music exist? 'German-Format Radio Analysis' is written for scheduling and music managers and goes deep into radio research and programming. It focuses on content and flow and presents new methods of analysing rotations and flows of music. The author, Harald Heckl, has been an employee at different radio stations for decades and is known as a critic of decreasing content on the radio and of computer-based music programming.